Effects of supplementation with Saccharomyces cerevisiae and aerobic training on physical performance of Mangalarga Marchador mares - Garcia, Tiago Resende (2015)
The objective of this study was to assess the effects of supplementation with Saccharomyces cerevisiae on the performance of Mangalarga Marchador equines and to verify the effectiveness of the aerobic training protocol adopted. The study used 14 Mangalarga Marchador mares in a completely randomized split-plot design. The plots were made up of two treatments (groups Probiotic and Control) and the split plots comprised two maximal-effort physical tests applied both before and after the six weeks of training. The animals’ spirometric parameters, heart rate, and plasma lactate levels were assessed. No difference was found between the Probiotic and Control groups in any of the parameters assessed. A difference was found in the physical tests for time-to-fatigue, aerobic and anaerobic thresholds, speed at which plasma lactate levels reached 2 and 4 mmol/L, speed at which the heart rate reached 200 bpm, and the lactate level at 30 min of the recovery period. Supplementation with Saccharomyces cerevisiae has no effect on physical conditioning of Mangalarga Marchador mares and the aerobic training protocol adopted increases the animals’ aerobic and anaerobic capacity.